2016
DOI: 10.5667/tang.2016.0025
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant and anti-inflammatory effects of Salix Koreensis Andersson in DC. leaf methanol extract in vitro models

Abstract: Oxidative rancidity in foods causes undesirable changes in nutritive value, aroma, flavor, and color. Salix Koreensis Andersson in DC. (SK) has anti-oxidative and anti-inflammatory effects and is traditionally used to treat neuralgia, edema, pain, and inflammatory diseases. However, the regulatory effects of SK on oxidative and inflammatory reactions have not been elucidated. In this context, we scientifically validated the anti-oxidative and anti-inflammatory activities of SK leaf (SKL). The methanol extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Altogether, our work has demonstrated the in vitro antioxidant capacity of TFW to a certain extent. Although previous studies have illustrated the antioxidant effects of willow bark and salix leaf extracts [ 30 , 31 ], our results regarding Willow Buds provide further evidence for the medical value of salix.…”
Section: Resultssupporting
confidence: 48%
“…Altogether, our work has demonstrated the in vitro antioxidant capacity of TFW to a certain extent. Although previous studies have illustrated the antioxidant effects of willow bark and salix leaf extracts [ 30 , 31 ], our results regarding Willow Buds provide further evidence for the medical value of salix.…”
Section: Resultssupporting
confidence: 48%
“…Salix koreensis Anderss (SKA; family Salicaceae), also reported as the Korean willow is a deciduous broad-leaved tree that grows in wetlands and is well distributed in East Asia, including Korea and China [ 19 ]. SKA has been reported to have antioxidant, anti-inflammatory, and hepatoprotective effects [ 20 , 21 ]. However, the effects of SKA on skin wound healing have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A pharmacological study of S. koreensis reported that the S. koreensis extract showed anticancer activity by inhibiting cell growth and promoting apoptosis in human colon and lung cancer cells [ 19 ]. S. koreensis extract also showed antioxidant, anti-inflammatory, and hepatoprotective effects [ 20 , 21 , 22 ]. Despite its diverse pharmacological effects, only a few studies have investigated the chemical constituents of S. koreensis .…”
Section: Introductionmentioning
confidence: 99%